Apnoeic oxygenation with nasal cannula oxygen at different flow rates in anaesthetised patients: a study protocol for a non-inferiority randomised controlled trial - Lorenz Theiler; Fabian Schneeberg; Thomas Riedel; Heiko Kaiser; Thomas Riva; Robert Greif (BMJ Open)
Introduction Apnoeic oxygenation using nasal high-flow oxygen delivery systems with heated and humidified oxygen has recently gained popularity in the anaesthesia community. It has been shown to allow a prolonged apnoea time of up to 65 min as CO2 increase was far slower compared with previously reported data from CO2 increase during apnoea. A ventilatory exchange due to the high nasal oxygen flow was proposed explaining that phenomenon. However, recent studies in children did not show any difference in CO2 clearance comparing high-flow with low-flow oxygen. To investigate this ventilatory exchange in adults, we plan this study comparing different oxygen flow rates and the increase of CO2 during apnoea. We hypothesise that CO2 clearance is non-inferior when applying low oxygen flow rates.Methods and analysis In this single-centre, single-blinded, randomised controlled trial, we randomly assign 100 patients planned for elective surgery to either control (oxygen 70 L/min, airway opened by laryngoscopy) or one of three intervention groups: oxygen 70, or 10, or 2 L/min, all with jaw thrust to secure airway patency. After anaesthesia induction and neuromuscular blockage, either one of the interventions or the control will be applied according to randomisation. Throughout the apnoea period, we will measure the increase of transcutaneous pCO2 (tcpCO2) until any one of the following criteria is met: time=15 min, SpO2 <92%, tcpCO2 >10.67 kPa, art. pH <7.1, K+ >6.0 mmol/L. Primary outcome is the mean tcpCO2 increase in kPa/min.Ethics and dissemination After Cantonal Ethic Committee of Bern approval (ID 2018–00293, 22.03.2018), all study participants will provide written informed consent. Patients vulnerable towards hypoxia or hypercarbia are excluded. Study results will be published in a peer-reviewed journal and presented at national and international conferences.Trial registration number This study was registered on www.clinicaltrials.gov (NCT03478774,Pre-results) and the Swiss Trial Registry KOFAM (SNCTP000002861).